Education and The Role of Midwife and Family Support in the Use of KIA Handbooks: A Comprehensive Approach - Ika Fitria Elmeida; Nurlaila; Nurchairina; Eva Berliana (Postgraduate, University of Mataram, 2025)
This study aims to explore the role of midwife and family support in the utilization of the Maternal and Child Health Handbook by pregnant women. Study used a quantitative cross-sectional design. The study site was the Kalianda Community Health Center, South Lampung, and included all pregnant women in their first to third trimesters registered with the KIA register. A purposive sampling method was used to select 120 pregnant women, involving 20 midwives as additional data sources. The research instrument, a structured questionnaire, was tested for validity and reliability, showing good results (validity coefficient r = 0.74–0.82; Cronbach's Alpha = 0.85). Data were collected through direct interviews by trained enumerators and analyzed using univariate and bivariate analysis techniques, including the Chi-square test. The results show the majority of respondents were aged 20–35 and had a relatively high level of education, which positively impacted their ability to understand health information. Good midwife support was significantly associated with the utilization of the KIA Handbook, with 83.3% of respondents who received good support successfully using the handbook. Family support also showed a positive influence, with 76.4% of respondents who received good support being able to use the KIA Handbook efficiently.